A prospective study comparing digital breast tomosynthesis with digital mammography in surveillance after breast cancer treatment. (July 2016) - Sia, Joseph; Moodie, Kate; Bressel, Mathias; Lau, Eddie; Gyorki, David; Skandarajah, Anita; Chua, Boon
Abstract: Background: Although the benefit of adjunct digital breast tomosynthesis (DBT) is established in population screening, its benefit in surveillance after breast cancer treatment is not well defined. We prospectively evaluated whether the addition of DBT to digital mammography (DM) reduced the rate of indeterminate findings compared to DM alone in patients after breast cancer treatment. Methods: Patients had both DM and DBT for routine surveillance. Two-dimensional synthesised mammogram (SM) was generated for each patient from DBT data. DM, SM, and DBT images were read for each patient by one of four radiologists credentialed for DBT. We compared the rates of indeterminate findings between DM + DBT with DM alone in patients with a range of breast densities and between DM and SM. Results: A total of 618 patients and 1069 breasts were analysed. The rates of indeterminate findings for DM + DBT versus DM alone were 10.5% and 13.1%, respectively (p = 0.018). In breasts treated with surgery and radiotherapy (n = 558), the corresponding rates of indeterminate findings were 4.9% and 6.9%, respectively (p = 0.039). The rate of indeterminate findings for DM + DBT increased with increasing breast density (p = 0.019). There was no significant difference in the rates of indeterminate findings between DM and SM (13.1% versus 11.5%, p = 0.1). Conclusion: The addition of DBT to DM reduced the rate of indeterminate findings in surveillance of patients after breast cancer treatment. Further research is required to confirm whether DBT and SM could replace DM for patients undergoing surveillance. Highlights: This is the first reported study investigating adjunct digital breast tomosynthesis (DBT) in surveillance after breast cancer treatment. Addition of DBT to digital mammography (DM) was associated with lower rate of indeterminate findings compared to DM alone. Synthesised mammograms reconstructed from DBT data had comparable rate of indeterminate findings with DM.